A Stress Reduction Program Adapted for the Work Environment: A Randomized Controlled Trial With a Follow-Up - Lacerda, Shirley S.; Little, Stephen W.; Kozasa, Elisa H. (Frontiers in Psychology, 2018)
Objective: The aim of this study was to evaluate an in situ stress reduction program, named PROGRESS, developed to meet the specific needs of workers in a business context and to research its impact upon non-severe psychiatric symptoms, stress, anxiety, depression, processing speed/attention and mindfulness. Methods: Participants with stress complaints were randomized into two groups: the main intervention group: group 1-G1, (n = 22); and the control group: group 2-G2, (n = 22). The protocol was divided into three distinct phases for the purpose of the study. Both groups were evaluated at time 1 (T1), before the first 8-week intervention, which only G1 received. The second evaluation was made on both groups at time 2 (T2), immediately after this first program; in order to test the program’s replicability and investigate possible follow-up effects, an identical second 8-week program was offered to G2 during time 3 (T3), while G1 was simply instructed to maintain the practice they had learned without further instruction between T2 and T3. A Confirmatory factor analysis (CFA) was conducted to investigate the construct validity of PROGRESS. Results: Repeated measures MANOVA test, comparing G1 and G2, showed the effect of the intervention from T1 to T2 (p = 0.021) and from T2 to T3 (p = 0.031). Univariate analysis showed that participants from G1 improved levels of non-severe psychiatric symptoms, anxiety, depression, stress, processing speed/attention and mindfulness when compared with G2, from T1 to T2 (p < 0.05). After the participants in G2 received the intervention (T2 to T3), this group also showed improvement in the same variables (p < 0.05). At the end of their follow-up period (T2-T3) – during which they received no further support or instruction – G1 maintained the improvements gained during T1-T2. The two main components were stress (stress in the last 24-h, in the last week and last month) and mental health (non-severe psychiatric symptoms, depression, anxiety and mindfulness). Conclusion: PROGRESS, an in situ mindfulness program adapted to fit within the reality of business time constraints, was effective at replicating in more than one group the reduction of stress, depression, anxiety, non-severe psychiatric symptoms, processing speed and also the improvement of attention skills, showing sustained improvement even after 8-weeks follow-up. Clinicaltrails.gov identifier: NCT02660307. https://clinicaltrials.gov/ct2/show/NCT02660307?term=Progress&rank=6